Perancangan alat pencacah limbah material 3D printer dengan metode Axiomatic House of Quality (AHOQ) - Benedikta Anna Haulian Siboro; Sintong Joshua Siahaan; Yosef Manik (Institut Seni Indonesia Yogyakarta, 2023)
Del Institute of Technology has Laboratorium Desain Produk (Lab Desprin) that based on additive manufacturing and 3D printer facilities. In its operation, the 3D printer uses acrylonitrile butadiene styrene (ABS) filament raw materials, polycarbonate (PC), polyvinyl alcohol (PVA), nylon, Poly Lactic Acid (PLA), Polyethylene (PE), Polypropylene (PP), and Investation Casting Wax. . The remaining filament and 3D printer printouts from the practical process require storage space in the laboratory. The material that makes up this filament itself is difficult to decompose by nature and has the potential to become harmful waste. This study aims to design a safe and practical 3D printer waste material chopper to recycle the remaining filament and 3D Printer printing results. With the Axiomatic House of Quality (AHOQ) method, the customer requirements for the enumerator are obtained, namely the appropriate size of the chop, has an indicator that it is on or not, safe in operation, not noisy, easy to move, and saves electricity. To meet this requirement, a waste chopper has been designed with specifications that it has a filter with a size that is adjusted to the desired chopping size, a cover on the material input channel as a security function and reduces noise, and uses a bicycle as a source of motion and saving electricity. The working system of the tool is a chopper tool by utilizing mechanical motion by rowing a bicycle as a source of motion for the chopper blade. This designed tool has been successfully built with the ability to chop materials with a thickness of > 15 mm and a noise level of less than 85 dB.